ANALISIS MANAJEMEN PENGELOLAAN OBAT PADA MASA PANDEMI DI PUSKESMAS SERING KECAMATAN MEDAN TEMBUNG - Fitriani Pramita Gurning; Sarah Fadhila Siregar; Ummi Rahmah Siregar; Ridha Rusmayanti; Fitria Nurhasanah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Drug management is a series of activities related to the aspects of planning, procuring, receiving, storing, destroying, controlling, recording and reporting drugs. During the Covid-19 pandemic, many activities were hampered, especially in drug management. This study aims to describe the management of drug management in the health center often in the sub-district of Medan Tembung. This type of research is descriptive research using a qualitative approach. The number of informants in this study were 3 people consisting of the head of the puskesmas, the person in charge of the pharmacy and the pharmacy staff. Data collection was carried out through in-depth interviews and direct observation. The results showed that the management of medicines had not been implemented properly in accordance with Permenkes number 74 of 2016 concerning standards of pharmaceutical services at Puskesmas. During a pandemic, the number of patient visits at the health center has often decreased drastically so that the planning and procurement of medicines that are prepared and available are many that are not used and even have expired in 2021. It can be concluded that the distribution and recording and reporting are in accordance with the drug management standards at the Puskesmas. However, planning, procurement and storage are not in accordance with existing standards. It is expected that the puskesmas will often pay attention to and follow the established management guidelines.